Iodide Functionalized Paper-Based SERS Sensors for Improved Detection of Narcotics - Tay, Li-Lin; Poirier, Shawn; Ghaemi, Ali; Hulse, John; Wang, Shiliang (Frontiers in Chemistry, 2021)
An inkjet-printed paper-based Surface-enhanced Raman scattering (SERS) sensor is a robust and versatile device that provides trace sensing capabilities for the detection and analysis of narcotics and drugs. Such sensors generally work well for analytes with good binding affinity towards the Au or Ag plasmonic nanoparticles (NPs) resident in the sensors. In this report, we show that iodide functionalization of the printed sensors helps to remove adsorbed contaminants from AuNP surfaces enabling superior performance with improved detection of narcotics such as fentanyl, heroin and cocaine by SERS. SERS signals are easily doubled with the iodide-functionalized sensors which also showed orders of magnitude improvement in detection limit. In this report, we show that a short (90 seconds) iodide treatment of the sensors significantly improved the detection of heroin. We propose that iodide functionalization be integrated into field detection kits through the solvent that wets paper-based sensor prior to swabbing for narcotics. Alternatively, we have also demonstrated that iodide functionalized sensors can be stored in ambient for up to one week and retain the improved performance towards heroin detection. This report will help to significantly improve the performance of paper-based sensors for field detection of narcotic drugs.